GeneXPress card: development and evaluation of educational card game for DNA transcription subtopics in genetics - Amani Norizan, Nurfarizah; Abu Bakar, Adibah; Saidin, Syazwan (International Journal of Evaluation and Research in Education (IJERE), 2025)
Understanding deoxyribonucleic acid (DNA) transcription poses a substantial challenge in studying genetics, often due to lack of understanding and traditional teaching methods that fail to engage students. This study introduces GeneXPress, an innovative card game, aimed at enhancing the learning experience of DNA transcription for higher education biology students. Using the ADDIE model, this preliminary study assessed the usability of the GeneXPress card game through a survey of 169 biology education students at Universiti Pendidikan Sultan Idris, Malaysia. A quantitative approach was employed to analyze the survey data, evaluating the game’s usability using descriptive statistics, including mean scores and standard deviations. The findings reveal high usability and positive views of GeneXPress, covering various aspects such as goals, design, components and organization, playability and usefulness, with average scores of above 3.79. The positive perception of GeneXPress among students highlights its ability to engage and motivate learners, making the study of complex genetic concepts more accessible and enjoyable. In conclusion, it underscores the vital role of innovative teaching aids in enhancing student engagement and understanding, paving the way for future explorations into educational tools that cater to the evolving needs of learners and educators alike.